Doped Carbon Nanoparticles as a New Platform for Highly Photoluminescent Dots - Sun, Ya-Ping (2008)
There have been rapid advances in the development and applications of semiconductor quantum dots (QDs) represented by CdSe/ZnS. However, a serious limitation of these QDs is the necessary use of toxic heavy metals. It is reported here that small carbon nanoparticles doped with inorganic salts serve as a highly promising new platform for brightly photoluminescent dots. The photoluminescent carbon dots with the carbon core doped with ZnO (C(ZnO)-Dots) or ZnS (C(ZnS)-Dots) in aqueous solutions are competitive to the commercially available CdSe/ZnS QDs in luminescence brightness.